HIGHER EDUCATION MINISTER URGES STUDENTS TO BECOME GRADUATES WHO ARE WILLING TO SERVE THE COUNTRY AND SOCIETY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 31 August 2016 – Students of Universiti Sains Malaysia (USM) are hoped to become assets to the country and be ever ready and willing to serve the society.